A contribution to the phytochemical survey of Peninsular Malaysia - Rahmani, Mawardi; Kiew, Ruth; Lajis, Md Nordin; Othman, Rahim; Toai, Robert F. (Universiti Pertanian Malaysia, 1985)
Specimens of 216 plants representing 150 genera and 50 families were collected from four areas in the western and central parts of Peninsular Malaysia. The leaves ofeach species were screened for alkaloids, steroids and triterpenes, and for saponins. 28 specz'es (13%) gave a positive test for alkaloids, 86 (40%) for saponins and 55 (25%) for triterpeneslsteroids.